India's five year plans - India. Planning Commission (Delhi, 2005)
The launching of the First Five Year Plan in April 1951 initiated a process of planned economic development of the country - aiming not merely at raising the standard of living of the people, but also opening out to them new opportunities for a richer and a more varied life. This was sought to be achieved by planning for growth and social justice. Indian economy has come a long way completing its nine Five-Year Plans and launching the 10th Five Year Plan in April, 2002 and which has already completed three years. The Planning Commission has just released the Mid-Term Appraisal of the 10th Five Year Plan (June 28, 2005). For the benefit of the readers and researchers, Academic Foundation has brought out this publication bringing at one source all the documents of Five Year Plans including the latest Mid-Term Appraisal of the Tenth Five Year Plan (Planning Commission Government of India). While Part I - Overview and Priority Areas for Action and list of recommendations of the Mid-Term Appraisal of the Tenth Five Year Plan, and Volume I of the Tenth Five Year Plan document is included in this book, the complete Mid-Term Appraisal of the Tenth Plan and all three volumes of the three volumes of the Tenth Plan Document along with the other nine documents of the earlier Fiver Year Plans (around 10,500 pages) are given in the accompanying CD-Rom offers inbuilt search facility, easy printout option, along with other usual advantages associated with the digital media.
Keywords: Five year plan-1951-56